'Startling; Nay, Almost Repulsive': Light Effects and Nascent Sensation in John Everett Millais's The Rescue. (1st October 2016) - Marshall, Nancy Rose
Abstract: Taking Pre-Raphaelite painter John Everett Millais's The Rescue (1855) as a case study of shifting aesthetic and moral frameworks, the essay investigates the ways in which mid-century British debates regarding the proper representation of light effects illuminate anxieties about a physically embodied viewer, one who encountered pictures in individualized ways that required regulation and guidance. Represented light, as an element that had a measurable effect on the senses, clearly stimulated a physical response and therefore brought the body to the fore in the art encounter. Types of painting that forcefully engaged the somatic self could become suspect and consequently subject to a process by which they were designated as 'sensation', a category in fraught relation with the disappearing 'sublime'. Combining close visual analysis, a discussion of The Rescue 's novel subject matter, remarks by its first beholders, and nineteenth-century aesthetic theory, the article reflects on the ways in which discourses of art revealed anxieties about the formation of the modern subject and argues that The Rescue is a node in which the death of the sublime meets the birth of sensation.